Changes in biomechanics of skiing at maximal velocity caused by simulated 20‐km skiing race using V2 skating technique - Ohtonen, O.; Lindinger, S. J.; Göpfert, C.; Rapp, W.; Linnamo, V. (Scandinavian journal of medicine & science in sports, 2018)
This study investigated how the fatigue caused by a 20‐km simulated skating cross‐country skiing race on snow affects the final spurt performance from a biomechanical perspective. Subjects performed a 100‐m maximal skiing trial before and at the end of the simulated race. Cycle characteristics, ground reaction forces from skis and poles, and muscle activity from eight muscles were recorded during each trial. Results showed that subjects were in a fatigued state after the simulated race manifested by 11.6% lower skiing speed (P<.01). The lower skiing speed was related to an 8.0% decrease in cycle rate (P<.01), whereas cycle length was slightly decreased (tendency). In temporal patterns, relative kick time was increased (10.9%, P<.01) while relative poling time was slightly decreased (tendency). Vertical ski force production decreased by 8.3% while pole force production decreased by 26.0% (both, P<.01). Muscle activation was generally decreased in upper (39.2%) and lower body (30.7%) (both, P<.01). Together these findings show different responses to fatigue in the upper and lower body. In ski forces, fatigue was observed via longer force production times while force production levels decreased only slightly. Pole forces showed equal force production times in the fatigued state while force production level decreased threefold compared to the ski forces.